The application of design of experiments in the hatchery wastewater treatment through biological method - Norazwina, Zainol; Aziz, Nor Hazwani, Aziz; Che Asilah Ilyana, Che Jazlan; Nurul Ain, Razahazizi (King Mongkut's Institute of Technology Ladkrabang, 2023)
This study was conducted to evaluate the most influential factors contributing to the removal of chemical oxygen demand (COD), nitrate-N, and total phosphorus in hatchery wastewater to optimize the removal process with the application of acclimatized mixed culture (AMC). The factors, namely, the ratio of AMC to synthetic wastewater (SW), support media, agitation speed, and retention times, were selected and were analyzed through two-level factorial analysis. The results suggested that the best conditions for maximum removal of each response was the ratio of 1 to 3 AMC: SW, absence of support media, 0 rpm agitation, and 4 days of retention time; where the removal values of COD, nitrate-N, and total phosphorus were 26.5%, 76.5%, and 42.9%, respectively. The two largest contributing factors obtained from the factorial analysis were analyzed by the Design-Expert software to determine the optimum conditions for waste removal through the central composite design of the Response Surface Methodology (RSM). The obtained removal values were up to 62%, 94%, and 46% for COD, nitrate-N, and phosphorus at each optimum condition. The results obtained were higher than those from factorial analysis for all responses. To sum up, the treatment of contaminated wastewater through biological treatment via acclimatized mixed culture can be applied. The optimum conditions determined from this study should bee helpful in scaling up the wastewater treatment process.